Recent Advances and Future Directions of Bioinformatics in Biomedical Engineering Perspective (International Journal of Innovative Research in Computer Science & Technology, 2018)
Bioinformatics is an interdisciplinary field  of biomedical engineering and biotechnology that  incorporates computational, mathematical, statistical  analysis and information technology to provide a  better solution to biological and biomedical  engineering problems. Bioinformatics aims at the  advancement of biomedical engineering by furnishing  an open platform for biomedical engineers,  researchers, educators, and scientists.Biomedical  engineering and bioinformatics is experiencing  remarkable expansion and recognition at present.  Applied bioinformatics is thus right now is a hot,  alluring and captivating field that incorporates life  sciences, biomedical sciences, computationl biology  and software engineering for better future of  mankind.
Keywords: Bioinformatics; collection; recognition